Association of Admission Platelet Crit with In-Hospital Outcomes in Non ST-Elevation Myocardial Infarction (NSTEMI) - Mushtaq, Huma; Shabbir, Muhammad; Mukarram, Shahid; Altaf , Maria (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the association of admission plateletcrit with in-hospital outcomes in non ST-elevation myocardial infarction (NSTEMI). Study Design: Analytical Cross-sectional study Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi; from Nov 2023 to Apr 2024 Methodology: Using non-probability consecutive sampling, 270 patients were included in this study. ECG findings were noted. Patients were divided into three tertiles based upon plateletcrit value such as T1=lower than normal PCT value (<0.21), T2=normal PCT(0.21-0.22) and T3= higher than normal PCT value (>0.22). PCT values were obtained from complete blood count sent at the time of presentation to AFIC emergency using Mandray BC 6200 CBC analyzer available at the AFIC pathology laboratory. Results: The study included 270 patients, out of which 137(50.7%) were males and 133(49.3%) were females and median age was 62.00(55.00-70.00) years. T1, T2 and T3 had 71(26.3%), 34(12.6%) and 165(61.1%) patients, respectively. Significant frequency differences of hypertensive and hyperlipidemia patients, and in-hospital outcomes were found between tertiles (p<0.01). Plateletcrit value was identified as an independent predictor for in-hospital outcomes including coronary revascularization (OR=0.08, 95% CI: 0.04-1.58, p<0.01), cardiogenic shock (OR=0.24, 95% CI: 0.15-0.37, p<0.01) and mortality (OR=0.04, 95% CI: 0.02-0.11, p<0.01), when adjusted for covariates. Conclusion: Plateletcrit value is an important predictor of in-hospital outcomes in NSTEMI patients, particularly coronary revascularization, cardiogenic shock, and mortality.